2012
DOI: 10.1108/17537981211225871
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and factor structure of a trait emotional intelligence measure in four Arab countries

Abstract: Purpose-The purpose of this paper is to examine the reliability and factor structure of the Arabic translation of the Emotional Intelligence Scale (EIS-41-A), a popular trait-based emotional intelligence test in Arab countries. Design/methodology/approach-A sample of 453 professionals from Egypt, Kuwait, Saudi Arabia and the UAE completed the EIS-41-A. Findings-Findings show that the Arabic scale did have acceptable reliability and demonstrated the same factor structure as the original English language scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…In addition, these findings are not consistent with previous research (Aritzeta et al, 2016;Mayer and Geher, 1996;Mandell and Pherwani, 2003;Alkhadher, 2006), with women scoring significantly higher than men, and they contradict those studies suggesting that in Arab countries females are taught to use and express more emotions than males (Mohamed et al, 2012). On the other hand, we find consistency with some studies conducted in China (Kong, 2017;Shi and Wang, 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, these findings are not consistent with previous research (Aritzeta et al, 2016;Mayer and Geher, 1996;Mandell and Pherwani, 2003;Alkhadher, 2006), with women scoring significantly higher than men, and they contradict those studies suggesting that in Arab countries females are taught to use and express more emotions than males (Mohamed et al, 2012). On the other hand, we find consistency with some studies conducted in China (Kong, 2017;Shi and Wang, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies conducted in Kuwait and other Gulf countries using various scales (Alkhadher, 2007;Alumran and Punam€ aki, 2008) have shown that females tended to score higher on EI measures than males. According to Mohamed et al (2012), one possible explanation is that, in the masculine Arab culture, girls are taught to show and use more emotions than boys. The researchers related this finding to the masculine Arab culture.…”
Section: Emotional Intelligence and Academic Successmentioning
confidence: 99%
See 1 more Smart Citation
“…professionals among four Arab countries Egypt, Kuwait, the UAE, and Saudi Arabia using an Arabic language emotional intelligence scale [29], which found that there are no signi cant differences between overall EI scores among the four Arab countries. However, using post hoc analysis, the authors could discern that Egypt has the lowest score on two factors; emotion regulation and utilization.…”
Section: Discussionmentioning
confidence: 98%
“…But, it had an antithesis which said that "teachers themselves have to learn the lessons with such difficulty before entering the classroom, let alone the students." (Mohamed, El Khouly, & Saad, 2012;Rojas-Méndez, Papadopoulos, & Alwan, 2015;Vassie, 2000;Wekke & Andriansyah, 2016). The different emphasizes in Arabic lesson on the importance of method and the importance of materials may occur built by the reality.…”
Section: Introductionmentioning
confidence: 99%